ANALISIS PARTISIPASI MASYARAKAT TERHADAP PELESTARIAN SITUS CAGAR BUDAYA SENDANG BEJI DESA KARANGPATIHAN, KABUPATEN PONOROGO - Sujud Tri Fajar Pamungkas; Hadi Cahyono; Prihma Sinta Utami (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
Abstract Local culture is one of the keys in the realization of the national culture of the Indonesian nation. Strengthening the preservation of local culture that is starting to become extinct, such as cultural heritage, requires the participation of the local community to make it happen so that it is maintained. The Sendang Beji cultural heritage site in Ponorogo Regency has a historical story that must be preserved so that it can be known by future generations. The purpose of writing this article is to reveal the results of research on community participation in the preservation of the Sendang Beji cultural heritage site, Ponorogo Regency. The method used in this study is a qualitative descriptive method with data collection techniques, namely interviews, observation and documentation. The results of this study indicate that the form of community participation fulfills 5 components forms of participation, namely: a) participation of ideas; b) energy participation; c) property participation; d) participation skills and skills; and e) social participation